2009
DOI: 10.1088/1367-2630/11/3/033011
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of Hardy's paradox by joint weak measurement with an entangled photon pair

Abstract: We implemented a joint weak measurement of the trajectories of two photons in a photonic version of Hardy's experiment. The joint weak measurement has been performed via an entangled meter state in polarization degrees of freedom of the two photons. Unlike Hardy's original argument in which the contradiction is inferred by retrodiction, our experiment reveals its paradoxical nature as preposterous values actually read out from the meter. Such a direct observation of a paradox gives us new insights into the spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
244
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(249 citation statements)
references
References 25 publications
5
244
0
Order By: Relevance
“…Recently, physicists performed a weak measurement and confirmed that the theoretically predicted and measured weak values showed good agreement [18].…”
Section: T Ih T T T T Ih T T Tmentioning
confidence: 77%
“…Recently, physicists performed a weak measurement and confirmed that the theoretically predicted and measured weak values showed good agreement [18].…”
Section: T Ih T T T T Ih T T Tmentioning
confidence: 77%
“…Weak value has a nature of being a complex number, which lead the weak measurements to provide an ideal method to examine some fundamentals of quantum physics. Quantum paradoxes (Hardy's paradox [17][18][19] and the three-box paradox [20]), quantum correlation and quantum dynamics [21][22][23][24][25][26], quantum state tomography [27][28][29][30][31][32], violation of the generalized Leggett-Garg inequalities [33][34][35][36][37][38] and violation of the initial Heisenberg measurement-disturbance relationship [39,40] are just few examples. In these typ-ical examples, the small effects have been amplified due to the benefit of weak values.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to notice that (11) is a sum, with coefficients given by 1 2 N i i i T  , which is a product of the following integrals:…”
Section: Generalized Bell Inequalitymentioning
confidence: 99%